Conceptual Distortion of Murabahah bil Wakalah and Its Implementation in Islamic Banking in Indonesia - Samsul; Bin Sapa, Nasrullah; Ambo Masse, Rahman; Rizal, Abdul; Jamaluddin (Universitas Islam Negeri Alauddin Makassar, 2023)
The Islamic banking products that are highly relevant to the current market needs include Murabahah bil Wakalah products. However, there is inconsistency between the concept and its implementation in Islamic banking institutions, both banks and non-banks. Therefore, this study aims to examine the distortion of the concept of Murabahah bil Wakalah with its implementation in Islamic banking institutions in Indonesia. Using descriptive qualitative research methods, through library research in collecting data from various sources such as scientific journal articles and Fatwas from the National Sharia Council of MUI. The data obtained were analyzed by literature review comparing the concept and implementation of the Murabahah bil Wakalah contract. The results of this study indicate that there are several distortions found in the concept of Murabahah bil Wakalah with its practice in Islamic banking, particularly in terms of giving representation (wakalah) and ownership issues of the object of the contract, which should rightfully belong to the buyer (Ba’i).